2019
DOI: 10.12681/jhvms.21790
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, genotyping and antimicrobial susceptibility of pathogenic Escherichia coli serotypes in ready to eat foods

Abstract: In this study, pathogenic Escherichia coli serotypes (E. coli O157:H7, O26, O111) and their molecular proximity and antimicrobial susceptibility were investigated in RTE foods. A total of 240 samples; consist of 105 stuffed mussel, 56 meatless cig kofte, 54 Russian salad, 25 cheese halva, were analyzed. The conventional culture and serotyping methods for determination of the organisms were performed and further confirmation by PCR was carried out. Confirmed E. coli O157 isolates were genotyped by the enterobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…However, another study revealed lower incidence (10%) of E. coli from oyster, while the peeled shrimp was free from E. coli infection (49). Lower isolation rate (2.8%) was detected in stuffed mussel in Turkey (50). The present study exhibited higher incidence of E. coli in smoked herring which might be owing to the mishandling during production and distribution process as previously explained (51).…”
Section: Incidence Of Escherichia Coli In Fast Foodsupporting
confidence: 49%
See 1 more Smart Citation
“…However, another study revealed lower incidence (10%) of E. coli from oyster, while the peeled shrimp was free from E. coli infection (49). Lower isolation rate (2.8%) was detected in stuffed mussel in Turkey (50). The present study exhibited higher incidence of E. coli in smoked herring which might be owing to the mishandling during production and distribution process as previously explained (51).…”
Section: Incidence Of Escherichia Coli In Fast Foodsupporting
confidence: 49%
“…Also, E. coli strains from retail meat in the United States were resistant to tetracycline and gentamicin with the percentages of 50.3 %and 18.6%, respectively (60). On the contrary, E. coli isolates from fast food showed lower resistance rates 29% for amoxycillin/clavulanic acid,14% for gentamicin and 29% for ciprofloxacin (50).…”
Section: Phenotypic and Genotypic Resistance Of Escherichia Coli From...mentioning
confidence: 99%